STRATEGI PEMERINTAHAN YANG DILAKUKAN KOMISI PEMILIHAN UMUM KOTA PEKANBARU DALAM MENINGKATKAN KUALITAS PENYELENGGARA PEMILU PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2019 (STUDI PADA KELOMPOK PENYELENGGARA PEMUNGUTAN SUARA) - Ilham, Muhammad; Kartini, Dede Sri; Yuningsih, Neneng Yani (Universitas Jenderal Ahmad Yani, 2024)
This study aims to find out and explain the Government Strategy Implemented by the Pekanbaru City General Election Commission in Improving the Quality of Election Organizers in the 2019 Presidential and Vice-Presidential Election (Study on Voting Organizing Groups). The concept used in this study is the concept of government strategy put forward by Geoff Mulgan, the indicators in this study include determining goals, analyzing the environment, determining directions, determining actions and analyzing learning. This study uses a qualitative descriptive research method, the data obtained through interviews, observations, and documentation. From the results of this study it can be seen that the strategy adopted by the Pekanbaru City General Election Commission in Improving the Quality of Election Organizers in the 2019 Presidential and Vice Presidential Election, the strategy set by the Pekanbaru City General Election Commission is considered capable of improving the quality of 2019 election organizers. However, there are problems, which in the recruitment process for KPPS organizers are still filled by community leaders who are old, have physical limitations and easily get tired, the timing of delivery of technical guidance is not quite right, the lack of interest in reading the instructions and technical guidelines of election organizers. With a strategy to improve the quality of election organizers in 2019 by the General Election Commission of Pekanbaru City, the authors hope that this strategy will not complicate Adhoc PPK, PPS and KPPS organizers, because the true purpose of improving the quality of election organizers is to provide a sense of security and public trust in the results of the implementation elections.